The Effect Of Using Problem-Based Learning (PBL) Model Towards Students’ Recount Text Writing Skills at Smp Methodist-9 Medan - Simanjuntak, Eva Dita Yanti; Sitorus, Nurhayati; Silitonga, Harpen H.P (Lembaga Riset dan Inovasi Almatani, 2024)
This study aims to determine whether the problem-based learning model can significantly influence the ability to write recount texts in grade 8 of Methodist-9 Medan Junior High School. This study used pre-experimental research with one group pre-test post-test design. This research design only looks at students' abilities before and after using a problem-based learning model. The sample of this research was 30 students of grade 8 of SMP Methodist-9 Medan. The data collection technique was conducted by writing test. The result of this study showed that there is an effect of problem-based learning model on the ability of grade 8 students in writing recount text at SMP Methodist-9 Medan. This is proved from the higher average score of students after using the problem-based learning model. The data in this study were also normally distributed. Based on data analysis by using t-test, it was found that Tcount was 16,50, at 5% significant level, dk(n-1)= 30-1=29, so Ttable =1,70. It can be concluded that Tcount >Ttable (16,50 > 1,70). It means that Ho was rejected and Ha was accepted. It’s means that the Problem-Based Learning Model significantly affects the eighth grade students’ ability in writing recount text at SMP Methodist-9 Medan.